Guinea-Bissau : 2010 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility and for Additional Interim Assistance Under the Enhanced Heavily Indebted Poor Countries Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Guinea-Bissau's 2010 Article IV Consultation and request for a Three-Year Arrangement under the Extended Credit Facility are discussed. Despite the difficult external environment and its political challenges, in 2009, Guinea-Bissau made progress in stabilizing its economy through the Emergency Post-Conflict Assistance-supported program. Real GDP growth reached 3 percent, driven by a favorable cashew harvest and a pickup in construction activity. The main risks relate to political instability, vulnerability to external shocks, and the possibility of inadequate donor support.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet